Performance Measurement in Kadipiro Village Government from Balance Scorecard Perspective - Rahmawati, Intan Fajar; Jatmika, Surya (Proceedings International Conference on Education Innovation and Social Science, 2022)
The purpose of this study was to determine the performance of the Kadipiro Village government as measured by the balanced scorecard method. This research uses qualitative research with case study design. The resource persons in this study were the village head, village secretary, village treasurer, head of the welfare section, chairman and secretary of the Village Consultative Body, head of RT, early childhood education teacher, and head of village youth and sports. Data collection techniques using interviews, observation and documentation. Data analysis techniques with data condensation, data presentation, and drawing conclusions. The results showed that the Kadipiro Village Government had good performance, (1) The service bureaucracy for the community was in accordance with procedures or rules including the service of making population documents that made it easier for the community, as well as community empowerment contained in the Village Government Work Plan that was right on target and brought many benefits to the community. Public. The Kadipiro Village Government in managing finances has used the SISKEUDES application which makes it easy to compile financial reports, puts forward the principle of transparency by providing an accountability report at the end of the year, namely the preparation of a Medium-Term Development Plan which will be submitted to the BPD, sub-district and district, in addition to reporting in the mass media so that known to the public. The infrastructure development contained in the Village Government Work Plan is right on target by building several facilities and infrastructure such as paving roads, concrete rebates, construction of embankments and bridge repairs. For a good village community security and order system, there is a security system in every RT. The village apparatus has carried out the main tasks of their respective authority functions in accordance with the Sragen Regency Regent Regulation Number 20 of 2017 concerning Organizational Structure and Village Governance.